Empowering the Next Generation: Bold Strategies to Combat Corruption and Foster Integrity Among Youth - Prakasa, Satria Unggul Wicaksana; Fatmawati, Ida Nuriya (Universitas Negeri Semarang, 2024)
Corruption remains a significant barrier to social, political, and economic progress globally, and the role of youth in shaping a more transparent and ethical society is crucial. This study explores effective strategies to combat corruption and instill values of integrity among young people. The research highlights the importance of anti-corruption education as a key strategy in overcoming corruption and building integrity. A collaborative effort between the Muhammadiyah Youth Branch Leader of Krembangan Branch and the Faculty of Law, University of Muhammadiyah Surabaya has led to the implementation of an anti-corruption education program in Morokrembangan Village. The primary goal of this initiative is to raise awareness, enhance knowledge, develop skills, and foster concrete actions among youth to actively fight corruption. The collaboration between youth, local government, and civil society is fundamental to the program's success, positioning it as a pioneering effort to combat corruption and build integrity at the grassroots level. The program is designed to provide participants with an in-depth understanding of the dangers of corruption and the importance of integrity in daily life. It equips youth with the practical knowledge and skills needed to recognize, report, and prevent corruption. Additionally, by involving youth in the oversight of development projects and promoting transparent community services, the program seeks to inspire similar initiatives in other regions. The study concludes by emphasizing that empowering youth through education, advocacy, and active participation is key to fostering a future generation committed to transparency, integrity, and accountability.